2005
DOI: 10.1111/j.1365-3164.2005.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism of progesterone by canine hair follicle cells

Abstract: Dermal papilla cells (DPC) and dermal fibroblasts (DFB) derived from hair follicles from two different body sites (head, flank) of four male, castrated beagle dogs were incubated for 24 h with radioactive progesterone (P4). Thin-layer chromatography was used for separation and autoradiography for identification of the radioactive metabolites. In DFB the main metabolites were cortisol and 4-pregnene-11beta-ol-3,20-dione, whereas in DPC they were 5alpha-pregnane-3,20-dione and cortisol. The highest percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Several studies have shown that cortisol can be detected in hair . Skin from humans and dogs is able to produce cortisol. The source of the hormone is not clear, and various possibilities have been considered in the literature (for example see Skobowiat et al .)…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that cortisol can be detected in hair . Skin from humans and dogs is able to produce cortisol. The source of the hormone is not clear, and various possibilities have been considered in the literature (for example see Skobowiat et al .)…”
Section: Discussionmentioning
confidence: 99%
“…Later studies (Keckeis et al 2012;Stubsjoen et al 2015) also suggest a possibility of local production of cortisol and intrafollicular autonomous cortisol synthesis. In addition, canine hair follicle cells in vitro are able to metabolise progesterone to cortisol (Bamberg et al 2005).…”
Section: Stress Hormonesmentioning
confidence: 99%
“…Canine hair follicles have been shown to express sex steroid receptors, 21 and their cells were shown to metabolize sex steroids. 22,23 Human hair follicles have been reported to function both as an estrogen target and as an estrogen source. 24 In conclusion, the findings of the present study support the use of deslorelin as an option for the treatment of intact male dogs with hair cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given that the pathogenesis of hair cycle arrest is still unclear, either adrenal gland‐derived hormones or other factors related to the hair follicle behaviour might be involved. Canine hair follicles have been shown to express sex steroid receptors, and their cells were shown to metabolize sex steroids . Human hair follicles have been reported to function both as an estrogen target and as an estrogen source …”
Section: Discussionmentioning
confidence: 99%